Effect of long-term constant irradiation on retinal glia - A. V. Potapov; E. Yu. Varakuta; A. V. Solonsky; S. V. Logvinov; A. V. Gerasimov; M. V. Svetlik; A. A. Zhdankina; E. A. Gereng; I. A. Petrov (Бюллетень сибирской медицины)
Aim. To study the response of retinal glial cells to constant irradiation of various intensity and to develop a mathematical model allowing to evaluate the dynamics of damage to radial glial cells and predict their photodamage depending on the duration and intensity of irradiation.Materials and methods. Outbred sexually mature white rats (n = 50) weighing 180–200 g were exposed to constant round-the-clock light (200, 3,500 lux, days 1, 2, 7, 14, 30). The control group consisted of 25 non-irradiated animals. Using semi-thin sections stained with toluidine blue, we counted the number of pycnomorphic cells in the radial glial cells. Ultrastructural changes in the glial cells were studied using the JEM-100 CX-II electron microscope.Results. The study showed that after photodamage, oligodendrocytes and astrocytes were mainly characterized by mitochondrial swelling and expansion of endoplasmic reticulum cisterns. Microglial cells at the late stage of the experiment (day 30) were localized in the inner layers of the retina; their density depended on the intensity of irradiation. The earliest (days 1, 2) changes in the radial glial cells were noted in the subretinal space and were manifested by proliferation of scleral processes and phagocytosis of dead sensorineural cell fragments. The intensification of destructive changes in the radial glial cells led to disturbances in neuron – glia interactions in the retina and a decrease in regeneration of retinal neurons (day 7–14). The developed mathematical model allowed to assess the dynamics of damage to the radial glial cells in the retina and to predict photodamage depending on the duration and intensity of irradiation.Conclusion. Glial responses in the retina after photodamage depend on the intensity and duration of light exposure. As the duration of irradiation increases, degenerative changes in glial cells intensify and are more pronounced after high (3,500 lux) irradiation intensity.